GENDER STEREOTYPES IN SELECTED CHILDREN’S SHORT CARTOONS - Đekić, Valentina M (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2022)
Looking at cartoon movies, children learn about masculinity and feminine, behavior, roles, expectations that shape fictional characters in stories shown in cartoon movies on television. The aim of the research is to determine what codes of film art and in what ways they convey gender stereotypes and how verbal and non-verbal means represent gender stereotypes as desirable and thus are a means in the process of socialization of children. The total duration of the observed material, all 65 episodes, in seven series, is 37,080 minutes, or about 10.30 hours. Sampling was conducted in March and April 2016. The results show that the cartoons that were the subject of the research, attracting the attention of children using the codes of film art, convey patriarchal social patterns, which is reflected in the gender socialization of children. However, a certain shift has been noticed, which indicates the maturing of the idea of ​​the importance of gender equality, which should be represented not only in the patriarchate, but in all gender systems that are hierarchical.
Keywords: children; cartoons; representation; television; gender stereotype